CHICKPEA PRODUCTIVITY DEPENDING ON WATER AND NUTRITION REGIMES OF THE SOIL IN THE ROSTOV REGION - G. V. Metlina; S. A. Vasilchenko; E. D. Krivosheeva (Зерновое хозяйство России, 2018)
Among all legumes chickpea is the most resistant and tolerant to heat and drought. But its productivity in the Rostov region is significantly dependent on soil water and nutrition elements content. The field trials were carried out in 2012–2016 in the laboratory of the cultivation technology of row crops in the FSBSI Agricultural Research Center ‘Donskoyʼ, located in the southern part of the Rostov region (town of Zernograd). The study showed that in the years with sufficient water content in soil chickpea productivity can reach 2.06 t/ha, in the years of drought productivity reduces to 1.34–1.54 t/ha. There has been determined a positive dependence of productivity on the reserves of productive moisture and available nutrition elements in the soil. The flowering (r = 0.63) and the germ phases (r = 0.59) in a meter soil layer showed the largest correlation between productivity and water reserves in soil. The largest coefficients of correlation between chickpea productivity and nitrate nitrogen (r = 0.63) and changeable potassium (r = 0.64) content in soil layer of 0–30 cm have been noted in the germ phase and mobile phosphorus (r = 0.76) content in soil layer of 0–30 cm have been noted in the flowering phase.